LOW TEMPERATURE IRON- AND NICKEL-CATALYZED REACTIONS LEADING TO COALBED GAS FORMATION - Medina J.C.; Butala S.J.; Bartholomew C.H.; Lee M.L. (My University, 2000)
Hydrocarbon hydrogenolysis and CO2 hydrogenation in the presence of Fe/SiO2 and Ni/SiO2 catalysts were evaluated as potential mechanisms contributing to natural gas formation in coalbeds. The hydrocarbons used as reactants in hydrogenolysis included butane, octane, 1-octene, and 1-dodecene. The reactions carried out in a laboratory batch reactor produced gas that contained methane concentrations greater than 90%, which resembles the composition of natural gas. Reaction temperatures were selected to resemble natural coalbed conditions. Evidence is presented to show that iron and nickel minerals, which can be present in coals at levels of 2000 and 10 ppm, respectively, can become active under geologic conditions. The oxides (Fe2O3 and NiO) used as precursors of the active catalysts (Fe and Ni metals) were reduced at 200°C under a hydrogen atmosphere. Mossbauer spectroscopy showed that ca. 6% of the iron oxide was converted to the metal; in the case of nickel, oxygen titration showed that the extent of reduction to the metal was ca. 29%. The resultant fractions of the active metals in coals are adequate to catalyze generation of appreciable amounts of methane over geologic time.